Modern Techniques for Fake News Detection in Social Media - Ganachari, Vinod; Gurav, Rohan (Journal of Social Science and Humanities, 2025)
We are living in a dynamic universe which is thoroughly information - centric and digitized. In present scenario, where mainstream media laps up everything said or done gets dished out forthwith it from different platforms. And there is nothing sacrosanct about one’s privacy; and gone are the days, when newspapers and audio - visual media outlets would hold strong sway on the society. But of late, menacing rise of social media has mercilessly siphoned off sheen surrounding mass media and latter’s mojo is out of sync with today’s reality. Notwithstanding, it is the social media that calls the shot as its algorithm operates with mindboggling speed in informing, spreading, and connecting people. But it is beset with menace called fake news that triggers distrust, doubts, and hiccups all around, hence, people dither to share even genuine news with others. We know, before fake news gets detected, it causes untold damages. Therefore, it is imperative to evolve some remedial mechanism and our study expounds its raison deter and delve into few approaches that enervate its viciousness.